2020
DOI: 10.1093/eurheartj/ehaa191
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive coronary microvascular dysfunction: a subclinical marker of end organ damage and heart failure

Abstract: Abstract Aims Hypertension is a well-established heart failure (HF) risk factor, especially in the context of adverse left ventricular (LV) remodelling. We aimed to use myocardial flow reserve (MFR) and global longitudinal strain (GLS), markers of subclinical microvascular and myocardial dysfunction, to refine hypertensive HF risk assessment. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 38 publications
2
25
0
5
Order By: Relevance
“…While a small proportion of patients with LV hypertrophy undergo myocardial infarction developing LV dilatation and heart failure, most patients progress directly to heart failure [ 187 ]. Abnormalities in microvascular function, structure, and perfusion may be responsible for the transition from hypertensive heart disease to LV dysfunction and heart failure in patients without epicardial CAD [ 188 , 189 ]. Microvascular rarefaction, perivascular fibrosis, and medial thickening of arterioles with reduced luminal areas have been observed in patients with hypertension without obstructive CAD [ 190 , 191 ].…”
Section: Cmd With Non-obstructive Atherosclerosismentioning
confidence: 99%
“…While a small proportion of patients with LV hypertrophy undergo myocardial infarction developing LV dilatation and heart failure, most patients progress directly to heart failure [ 187 ]. Abnormalities in microvascular function, structure, and perfusion may be responsible for the transition from hypertensive heart disease to LV dysfunction and heart failure in patients without epicardial CAD [ 188 , 189 ]. Microvascular rarefaction, perivascular fibrosis, and medial thickening of arterioles with reduced luminal areas have been observed in patients with hypertension without obstructive CAD [ 190 , 191 ].…”
Section: Cmd With Non-obstructive Atherosclerosismentioning
confidence: 99%
“…26 Myocardial mechanics is linked to coronary microvascular dysfunction in patients with hypertensive HF. 27,28 In AHF, cardiac sympathetic nerve dysfunction, as evaluated by 123 I-metaiodobenzylguanidine imaging, is associated with poor outcome irrespective of LVEF. 29…”
Section: Biomarkerimentioning
confidence: 99%
“…27 More importantly, a recent study demonstrated significant associations between CMD and impaired GLS and future HF risk in hypertensive patients. 28 Although higher UACR was significantly associated with worse diastolic dysfunction defined by lower e′ and higher E/e′, these relationships were attenuated after multivariable adjustment. There are conflicting findings with respect to the association between UACR and diastolic function.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, CMD was associated with a markedly increased risk of HFpEF 27 . More importantly, a recent study demonstrated significant associations between CMD and impaired GLS and future HF risk in hypertensive patients 28 …”
Section: Discussionmentioning
confidence: 96%